CARA MAHASISWA FDIK MENGHADAPI DAMPAK COVID 19 PADA MASA PEMBERLAKUAN PSBB - Nazirman Nazir; Rini Novianti Rini (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2020)
ABSTRAK This article discusses various methods undertaken by students of the Da'wah Faculty of Islamic Studies Imam Bonjol Padang in addressing the implementation of the Large-Scale Social Limitation by the Government in order to break the chain of transmission and transmission of Covid. 19. The purpose of writing this article is to offer an alternative concept of problem solving specifically in relation to the covid effect 19 among students of the Imam Bonjol UIN FDIK Padang since being treated by the PSBB, which was protected from April 22 to May 28, 2020. The focus of this article discusses the conditions , views of the attitudes and ways of students in responding to government policies in relation to the activities of teaching and learning during the PSBB period. The method used in this research is descriptive quantitative with online survey data collection techniques using gooleform media with percentage descriptive analysis techniques. The findings of this reset illustrate that in general students view covid as a test and disaster that needs to be dealt with with wisdom. The general action taken by students is to obey the rules of Covid health protocol and implement the activities of learning at home